Investigating antibiotic use in Gaza Strip hospitals: A retrospective cross-sectional analysis - Hala ZI Alagha; Maha Jebreel Al Telbani (Journal of Infection in Developing Countries)
Introduction: Rates of antimicrobial resistance in the Gaza Strip are rising while regulations on antibiotics use are weakly implemented. This study aimed to investigate antibiotic use in hospitals utilizing World Health Organization (WHO) hospital, prescribing, and patient care indicators.